Analysis of tool wear, cutting force, surface roughness and machining temperature during finishing operation of ultrasonic assisted milling (UAM) of carbon fibre reinforced plastic (CFRP) - Abd Halim, Nor Farah Huda; Ascrofta, Helen; Barnes, Stuart (Elsevier, 2017)
Carbon fibre reinforced plastic (CFRP) is typically manufactured near to net-shape. However, secondary machining processes such as milling are often required before final assembly operation. Conventional milling is often associated with challenges such as rapid tool wear, poor surface roughness, fibre pull-out, delamination and high cutting forces. The present work compares ultrasonic assisted milling (UAM) with conventional milling (CM) of CFRP in term of tool wear, cutting force, surface roughness, and machining temperature. Experiments for UAM and CM were conducted using three fluted polycrystalline-diamond (PCD) tools employing constant speed (500m/min) and feed rate (0.8m/min). For UAM, the amplitude and frequency were fixed at 5μ m and 39000 Hz, respectively. Application of UAM resulted in reduced forces (up to 20 %) and temperatures (up to 15 %), however, it was observed that surface roughness increased (up to 5 %). In addition, UAM produced higher tool wear (106 μ m) when compared to CM (80 μ m) after 10m machining length. Analysis of thermal damage of machined surface using Different Scanning Calorimetry (DSC) is also presented. The glass transition temperature (Tg) of CFRP shifted from 272 °C to ≈70 °C for both UAM and CM suggesting that machining temperature resulted in significant material property changes.